Can commercially available mosquito nets be used for rearing sandfish (Holothuria scabra) juveniles in floating ocean nursery? - Margarita de la Torre-de la Cruz; Jonh Rey L. Gacura; Racelle R. Rescordado; Janine L. Villamor (Marine and Fishery Sciences, 2023)
This study investigates the potential of locally available mosquito nets as an alternative material for sandfish ocean nurseries. Mosquito nets (~ 2 mm mesh) were designed into single (SL), double (DL), and triple-layered (TL) to approximate the conventional hapa (CH) with ~ 1 mm mesh normally used in sandfish ocean nurseries. The study was conducted in Maliwaliw island and in a cove in Buyayawon both located in Eastern Samar, Philippines. Results showed that TL had the highest juvenile survival (35.93 ± 10.56%) in Maliwaliw, which was significantly different (p < 0.05) from SL and DL. The DL design showed the highest survival (25.23 ± 17.15%) in Buyayawon by day 60, followed by TL (21.37 ± 3.11%), although not statistically significant. On the other hand, average growth rate was highest in SL in both sites where survival was also the lowest. Biomass, however, was the highest in DL in Buyayawon (1,014 ± 266 g m-2) followed by TL in Maliwaliw (925 ± 107 g m-2). Sandfish juvenile survival in DL and TL were higher than those in the CH in both sites suggesting that mosquito nets can indeed be used as an alternative material for rearing early-stage sandfish juveniles in floating ocean nurseries.